Evaluation of Al Islam Kemuhammadiyahan Curriculum in University of Muhammadiyah Gresik - Basri, Hasan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Evaluating the curriculum in higher education is a complex and multifaceted process. Changes in the curriculum of the al-Islam Kemuhammadiyahan course at the Universitas Muhammadiyah Gresik became a challenge for lecturers in preparing semester learning plans and implementation of learning to adjust to the National Standards of Higher Education because in addition to being a national compulsory subject known as Islamic Religious Education with the number 2 credits are also compulsory courses at the Universitas Muhammadiyah Gresik. This study uses the Countenance evaluation model with two main matrices in describing descriptions and judgments. As for the results of this research, the documents in the al-Islam Kemuhammadiyahan semester learning plan have met the National Standards of Higher Education criteria, but the learning methods section and assessment indicators do not meet the National Standards of Higher Education criteria. The learning process of the al-Islam kemuhammadiyahan shows a discrepancy with the semester learning plan of the Kemuhammadiyahan al-Islamic course due to ineffective use of time in the learning process. Students can understand and try to practice the basics of the Islamic religion well.